Step-by-step explanation:
X(x+6) - 6(x+6)
X+6x-6x-36
X-36
Answer:
89,709
Step-by-step explanation:
∡Z= 54°
tan 54 = XY / 361
XY = 361 · tan 54°
XY = 497
A = 1/2 (361) (497)
Answer:
Minimum: (2,4)
Step-by-step explanation:
h(x)=3(
-4x)+16
=3(
-4x+4-4)+16 (- For the balance of equation, and attention 1)
=3
-3*4+16
=3
+4
<h3>Attention:</h3>
1. ![(a-b)^{2}=a^{2} -2ab+b^{2}](https://tex.z-dn.net/?f=%28a-b%29%5E%7B2%7D%3Da%5E%7B2%7D%20%20-2ab%2Bb%5E%7B2%7D)
2. The formula for the vertex form is y =
, the vertex is (h,k)
Answer:
g(x) = –3(x + 6)2 + 48.
Step-by-step explanation:
The graph of f(x) = x2 is shifted right 6 units. The graph of f(x) = x2 is shifted down 48 units. The graph of f(x) = x2 is reflected over the y-axis.
Answer:
sorry im on a time lapse, so the answer is 2 1/2. hope it helps
Step-by-step explanation: